2016
DOI: 10.12738/estp.2016.5.0137
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition, Strategies, Achievement, and Demographics: Relationships Across Countries

Abstract: Learning strategies, such as memorization and elaboration strategies, have received both support and repudiation. The 2009 international PISA reading, science, and mathematics achievement test and survey of 15 year-olds in 65 countries was used. The findings indicated that self-reported use of learning strategies, which involve compensatory approaches like memorization, across a global sample was not strongly associated with higher achievement. However, metacognitive strategies which involve an awareness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
(36 reference statements)
3
5
0
Order By: Relevance
“…This corroborates the idea that the two components of cognition, although complementary, are independent and may play different roles in the cognitive processes (Callan et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This corroborates the idea that the two components of cognition, although complementary, are independent and may play different roles in the cognitive processes (Callan et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Some students, on the other hand, may perform poorly in their academic studies because they are neither prone nor instructed to effectively use their metacognitive skills. As suggested by Callan, Marchant, Finch, and German (2016), metacognitive strategies remained a significant predictor of achievement. Therefore, there is a need to examine how metacognitive dimensions influence our students' academic performance.…”
mentioning
confidence: 73%
“…According to the results of SEM, metacognition positively influences mathematical modelling competency. The expected positive effects of metacognition on students' mathematical modelling competency corroborate previous research findings in mathematics achievement (Bonnett et al, 2016;Callan et al, 2016;Özcan, 2016;Tzohar-Rozen & Kramarski, 2014) and problem solving skills (Yusnaeni & Corebima, 2017). Other studies indicated that metacognition influences the modelling strategy development of students when the effects of four metacognitive components are taken into consideration (i.e., awareness, planning, cognitive strategy, and self-checking) (Yildirim, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…The difference in metacognition between men and women is influenced by learning strategies. This is in line with the results of research Callan et al [26] that there are significant differences between how men and women utilize learning and metacognitive strategies. In addition, the results of Bahrami & Yousefi's research [27] show that a significant difference was observed between girls and boys in thinking anxiety (health anxiety, social anxiety, and meta-worry).…”
Section: Discussionsupporting
confidence: 91%